(3MdjI GdeMGVQI aj UfGYI GdTYQ hCfhGYgs - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s ((3EHQGgje Hf eMeO GdZSGfj GdTgjQ HGdhRjQ s)
(3ChdgG (B:s
(3gPG HGH aj fXe GdefKhQ bGd CHhYdj(B: (3hef GdTYQGA GdeWHhYjf WGFaI JNai GdTYQ GYJeGOG Ydi efKhQ GdcdGe Ohf efXheg s
(3BNQgG (B:s
(3cUOY GdRLGLI eG JSJWjY ca GdUfGY dg Cf JMjQG s
(3ef fSNI KGfjIs
(3HChdgG JMHjS Ydi LGeY GdbQhjjf SfI (B1118(3g`s
(3YdjgG ebGHdIs
(3hjHOh Cf GdLRA JcedI ddfSNI GdSGHbI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs